Contested Sustainability The Political Ecology of Conservation and Development in Tanzania - Ponte, Stefano; Noe, Christine; Brockington, Dan; Mwamfupe, Asubisye; Gallemore, Caleb (Eastern Africa Series, 2022)
Providing valuable insights into the successes and failures of the management of wildlife, forests and coastal resources in Tanzania, this study draws from 'New Partnerships for Sustainability' (NEPSUS), a 5-year collective research project. Responding to the urgent need in writings on conservation, sustainability and development, this book considers how politics structure sustainability outcomes at multiple levels, it uncovers the complexity of partnerships that are crucial for achieving this, challenging its readers to interrogate these sustainability networks and their environmental and socio-economic outcomes. The contributors, from a range of disciplines, compare 'more complex' partnerships to relatively 'simpler', more traditional top-down and centralized management systems and to location where sustainability partnerships are not in place. Within-sector comparisons allow a fine-tuned analysis that is formed of historical, location and resource-specific issues, which can be used as input for resource-specific policy and partnership design. Experiences and lessons can be drawn from comparisons across the three different sectors, which can be applied to natural resource governance more broadly.